2021
DOI: 10.1038/s41372-021-01033-6
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a neonatal platelet transfusion guideline to reduce non-indicated transfusions using a quality improvement framework

Abstract: Objective Variation exists in neonatal platelet transfusion practices. Recent studies found potential harm in liberal platelet transfusion practices, supporting the use of lower transfusion thresholds. Our aim was to reduce non-indicated platelet transfusions through implementation of a restrictive platelet transfusion guideline. Study design Platelet transfusions from January 2017 to December 2019 were classified as indicated or non-indicated using the new guideline. Interventions included guideline implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Another retrospective comparison of two cohorts of preterm infants with BW <1500 g before (2002–2004, N = 121) and after (2004–2006, N = 134) restrictive platelet transfusion guideline implementation in the same NICU reported a 40% decrease in platelet transfusions following restrictive guidelines 12 . More recently, a study compared the number of non‐indicated platelet transfusions before ( N = 1388) and after ( N = 678) implementation of a restrictive platelet transfusion guideline in the Boston Children's Hospital NICU in January 2019 13 . The rate of non‐indicated platelet transfusions according to the restrictive guideline decreased from 12.5% to 2.9%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another retrospective comparison of two cohorts of preterm infants with BW <1500 g before (2002–2004, N = 121) and after (2004–2006, N = 134) restrictive platelet transfusion guideline implementation in the same NICU reported a 40% decrease in platelet transfusions following restrictive guidelines 12 . More recently, a study compared the number of non‐indicated platelet transfusions before ( N = 1388) and after ( N = 678) implementation of a restrictive platelet transfusion guideline in the Boston Children's Hospital NICU in January 2019 13 . The rate of non‐indicated platelet transfusions according to the restrictive guideline decreased from 12.5% to 2.9%.…”
Section: Discussionmentioning
confidence: 99%
“…12 More recently, a study compared the number of non-indicated platelet transfusions before (N = 1388) and after (N = 678) implementation of a restrictive platelet transfusion guideline in the Boston Children's Hospital NICU in January 2019. 13 The rate of non-indicated platelet transfusions according to the restrictive guideline decreased from 12.5% to 2.9%. In all three studies, the rates of adverse outcomes such as NEC, IVH, other major bleeding and mortality remained stable.…”
Section: Discussionmentioning
confidence: 99%
“…Through a range of strategies, the authors reported a decrease in unnecessary (potentially harmful) platelet transfusions from a rate of 12.5 to 2.9 per 100 patient admissions over a 3-year period. 27 Many other potential strategies to enact change have been described in medicine, including audit and feedback, automated reminder systems, and use of opinion leaders [28][29][30][31][32] (Table 2).…”
Section: Differential Rates Of Acceptance Of Effective Evidence-based...mentioning
confidence: 99%
“…A first step considered the quality of the evidence and breadth of short‐term and long‐term outcomes reported, as described previously. Through a range of strategies, the authors reported a decrease in unnecessary (potentially harmful) platelet transfusions from a rate of 12.5 to 2.9 per 100 patient admissions over a 3‐year period 27 …”
Section: So What?mentioning
confidence: 99%
“…Until then, in the absence of national guidelines, a judicious, evidence-based approach to neonatal platelet transfusions is the best clinical strategy. 2,17…”
mentioning
confidence: 99%